Treatment of Severe Japanese Encephalitis Complicated With Hashimoto’s Thyroiditis and Guillain-Barré Syndrome With Protein A Immunoadsorption: A Case Report - Zang, Qiuling; Wang, Yating; Guo, Junshuang; Long, Liyang; Zhang, Shuyu; Cui, Can; Song, Dandan; Yu, Boguang; Tang, Fenlan; Teng, Junfang; Miao, Wang (Frontiers in Immunology, 2022)
A severely comatose patient was diagnosed with Japanese encephalitis(JE), and their condition became complicated with Hashimoto’s thyroiditis(HT) and Guillain-Barré syndrome(GBS). After antiviral, glucocorticoid, and immunoglobulin treatment, the patient’s consciousness was restored and she could breathe spontaneously, but new-onset, primarily demyelinating GBS developed, which progressed to demyelination combined with axonal injury. The patient was switched to protein A immunoadsorption(PAIA) therapy, and her Hughes score decreased rapidly, from 4 to 1 after 6 months. This patient was the first in whom a PAIA combined with antiviral-hormone-gamma globulin regimen was used to treat encephalitis, meningitis, HT, and GBS caused by JEV infection, thus reflecting the good clinical application value of PAIA in the treatment of immunological complications of JE.